Predictors of fever response in tuberculous meningitis: A clinical, MRI and biomarker study. (2nd November 2021) - Kalita, Jayantee; Pandey, Prakash C.; Shukla, Ruchi; Haldar, Rudrashish
Abstract: Background: Central nervous system (CNS) has a different immune surveillance system; therefore, fever at admission and timeline of fever response after antitubercular treatment (ATT) may follow a different course in CNS infection. We report the predictors of fever response in tuberculous meningitis (TBM) including the effect of tumour necrosis factor‐α (TNF‐α) in cerebrospinal fluid (CSF) and its gene expression at mRNA of peripheral blood mononuclear cells (PBMCs). Methods: Fifty‐seven patients with TBM were prospectively evaluated. Their clinical findings and severity of meningitis were recorded. The expression of TNF‐α gene in PBMCs was quantified by real‐time polymerase chain reaction and TNF‐α concentration in CSF by cytokine bead array both in the patients and 14 matched controls. Results: All the patients had history of fever for a median duration of 75 days. The admission temperature ranged between 37.2°C and 40°C and correlated with CSF cell counts ( p < 0.05). Cranial MRI was abnormal in 54 (94.7%) and revealed exudates in 33(57.9%), hydrocephalus in 27(47.4%), infarction in 27(47.4%) and tuberculoma in 33(57.9%) patients. Fever subsided after a median duration of 18 (2 60) days of treatment. Twelve (21.8%) patients only became afebrile within 10 days. The expression of TNF‐α gene correlated with CSF concentration of TNF‐α ( p = 0.02) and independently predicted duration of defervescence [adjusted hazard ratio 1.02 (95% CI 1.00–1.04; p = 0.01). Conclusion: In the patients with TBM, defervescence takes longer time, and TNF‐α gene expression predicts the duration of defervescence. Future studies are needed to evaluate the role of TNF‐α‐modifying drugs in TBM.